IL-6 During Influenza-Streptococcus pneumoniae Co-Infected Pneumonia—A Protector - Gou, Xuemei; Yuan, Jun; Wang, Hong; Wang, Xiaofang; Xiao, Jiangming; Chen, Jingyi; Liu, Shuang; Yin, Yibing; Zhang, Xuemei (Frontiers in Immunology, 2020)
Understanding of the mechanism underlying pathogenesis or protection for influenza-Streptococcus pneumoniae coinfected pneumonia provides potential strategy in decreasing the high morbidity and mortality of this infectious disease. Interleukin-6 (IL-6) is an important cytokine to limit infection-related inflammation; however, its role in this coinfected pneumonia remains unclear. Here we show that patients with the coinfected pneumonia displayed dramatically elevated IL-6 levels; similarly, the clinically relevant coinfected mice had increased IL-6 production in the lung and circulation. IL-6-/- mice showed increased bacterial burden and also facilitated early dissemination of bacteria to extrapulmonary sites accompanied by aggravated pulmonary lesion and mortality in coinfected pneumonia. This protection of IL-6 was associated with cells apoptosis and impaired macrophages function. Importantly, therapeutic administration of recombinant mouse IL-6 protein improved the survival of cells in BALF, and enhanced macrophages phagocytosis activity through increased MARCO expression. This protective immune mechanism will help to understand the potential impact of immune components and provide potential therapeutic options in influenza-Streptococcus pneumoniae coinfected pneumonia.